Pakan suspensi daging kekerangan bagi pertumbuhan benih sidat (Anguilla bicolor) - Koroh, Pieter A; Lumenta, Cyska (Universitas Sam Ratulangi, 2014)
Abstract The objective of this research was to evaluate the effect of different mussel flesh suspension feed in providing best growth and feed efficiency on eel seeds, Anguilla bicolor. Treatment feed included A (kijing Taiwan Anodonta woodiana Lea)), B (keong mas Pomacea canaliculata), C (kerang darah Anadara granosa) and D (commercial pellet), each with three replications. Elver was reared in plastic container having diameter of 40 cm. Research results showed the best relative growth and feed efficiency were achieved in treatment A with relative growth 64.95% and feed efficiency 4.41, followed by treatment C (relative growth 40.97% and feed efficiency 2.73), Treatment D (relative growth 32.71%% and feed efficiency 2.23), and treatment B (relative growth 31.61% and feed efficiency 2.17). During the experiment, water temperature was 26-28oC and pH 7 which were suitable for growth and survival of eel seeds. As conclusion, the use of suspension food of kijing taiwan mussel resulted in the best relative growth and food efficiency. Keywords: elver, fish feed, mussel, growth, food efficiency